Analysis of the Effect of Macroeconomics on Net Assets Value (NAV) of Sharia Mutual Funds in Indonesia - Nafisah, Hilyatun; Supriyono (International Journal of Islamic Business and Economics (IJIBEC), 2020)
Net Asset Value (NAV) is a measure of investment performance for sharia mutual funds derived from the entire value of the mutual fund portfolio fewer liabilities. This research aims to analyze the effect of the rupiah exchange rate, inflation, Jakarta Islamic Index (JII) and Bank Indonesia Sharia Certificate (SBIS) on Net Asset Value (NAV) of Sharia Mutual Funds. The object in this research consisted of 5 companies registered with the Financial Services Authority (OJK) from 2012-2019. Panel data regression analysis was used to test the hypothesis in this study. A random effect is used to determine the differences in the effect. The result of this study concluded that rupiah exchange rate, inflation and JII and SBIS effect on NAV of sharia mutual funds simultaneously. Partially, an unstable rupiah exchange rate is considered to have an impact on the company's production factors and affect the validity of the stock price; This causes investments no longer be attractive to investors, thereby reducing the value of investments that have an impact on the declining mutual fund NAV. Inflation decreases the real income of people with fixed income will also reduce the value of wealth in the form of money so that people will prefer to invest their money in the form of real assets that will result in reduced investment in the financial and capital markets and lower the NAV value of Islamic Mutual Funds. JII describes the performance of stocks which are one of the portfolios of sharia mutual funds. If the JII index value rises, then the increase in the portfolio of sharia mutual funds that share type will also rise which will have an impact on the increase in the nett asset value of sharia mutual funds. SBIS does not affect the Sharia Mutual Funds NAV. The relationship between SBIS and the Sharia Mutual Fund NAV as well as the relationship between interest rates and stock prices is negative or in the opposite direction. If interest rates rise at an adequate level, investors will try to move their investments from stocks to deposits.